Investigating gaming disorder and individual differences in gaming motives among professional and non-professional gamers: An empirical study. (November 2022) - Montag, Christian; Schivinski, Bruno; Kannen, Christopher; Pontes, Halley M.
Highlights: Professional gamers and non-professional gamers were contrasted regarding their gaming motives. Professional gamers and those intending to become one are rather similar regarding their gaming motive expressions. Gaming motives are also linked to gaming disorder tendencies. Abstract: The present study investigates the relationship between Gaming Disorder (GD) and individual differences in gaming motives and how they might differ between three groups of gamers. The first group stated to be professional gamers ( n = 129; 2, 49%), the second group consisted of non-professional gamers, who intended to become professional gamers ( n = 646; 12, 45%), and the third group included the remaining non-professional gamers ( n = 4, 412; 85, 06%). Gaming motives were assessed via the Motives for Online Gaming Questionnaire (MOGQ), and GD was assessed with the Gaming Disorder Test (GDT). Results revealed that professional gamers and those intending to become professional were very similar regarding their gaming motive expressions. In contrast, non-professional gamers without esports ambitions scored significantly lower on all gaming motives, except for the recreational motive which was comparable across all groups. Several consistent gaming motive-GD associations appeared across the three gamer groups, with the most robust finding being that higher escapism motive expressions relate to greater GDT scores. The present study sheds light on an emerging field of research attempting to better understand competitive gaming in the context of esports.